Multilocus molecular systematics of the circumtropical reef-fish genus Abudefduf (Pomacentridae): history, geography and ecology of speciation - Campbell,Matthew A.; Robertson,D. Ross; Vargas,Marta I.; Allen,Gerald R.; McMillan,W.O. (PeerJ, 2018)
We investigated a pantropical sub-family and genus of damselfishes, the sergeant-majors (Pomacentridae: Abudefdufinae: Abudefduf), to identify the tempo and mechanisms of speciation in the lineage. We examined sequence capture data from 500 loci and 20 species, with multiple individuals sampled from across the geographic ranges of widespread species. Utilizing a maximum likelihood framework, as well as a time-calibrated Bayesian phylogeny, the following key questions are addressed: What is the historical tempo of speciation? What are the relative contributions of vicariant, peripatric and parapatric speciation to sergeant-major diversity? How is speciation related to major variation in trophic ecology? The approximately 20 species of sergeant-majors fall into three main lineages. The ancestral condition appears to be benthivory, which is predominant in two lineages comprising six species. The remaining species of sergeant-majors, of which there are at least 15, fall within a clade composed entirely of planktivores. This clade is sister to a benthivore clade that included one species, Abudefduf notatus, in transition to planktivory. Most speciation of sergeant-majors, which appeared ∼24 million years ago, occurred in the last 10 million years. Present distributional patterns indicate vicariant speciation precipitated by the closure of land barriers between both sides of the Atlantic and the Pacific, and the emergence of land between the Indian and Pacific Oceans. Within this backdrop, frequent oscillations in sea level over the last 10 million years also appear to have generated conditions suitable for both peripatric and vicariant speciation, and most speciation within the genus appears linked to these changes in sea level. Diversification within the genus has been concentrated in planktivorous seargeant-majors rather than benthivores. The root cause is unclear, but does not appear to be related to differences in dispersal potential, which is greater in the planktivorous species, due to the ability of their post-larval juveniles to raft with floating debris. This elevated speciation rate in planktivores and their propensity to form local endemics may reflect relaxation of selective pressures (e.g., on crypticity) that limit speciation in benthivorous sergeant-majors. Finally, our data allow us to clarify relationships of geminate sergeant-major species, indicating that there are subdivisions within the Atlantic for both benthivore and planktivore geminate pairs that may have misled previous studies.
Keywords: Abudefdufinae; Sergeant-majors; Isthmus of Panama; Vicariance; Feeding mode; Phylogenetics